Are Mechanical and Biological Techniques Efficient in Restoring Soil and Associated Biodiversity in a Brownfield Site? - Guillaume Jacek; Anne Rozan; Isabelle Combroux (Land, 2022)
Brownfield technosol restoration represents a real opportunity to minimize land consumption, but it often requires intensive intervention and reconstruction, leading to soil donor site destruction and potential pollution. Using a former oil refinery brownfield site, this research compares the short-term (one year) impact of localized restoration methods, including soil surface scarification, organic matter addition, earthworm inoculation (locally and commercially sourced), on the soil fauna and vegetation properties. Vegetation rapidly covered the bare soil, but few significant impacts were observed in terms of the soil or vegetation structure. The initial positive impact of soil scarification on surface compaction quickly faded and earthworm inoculations did not seem to impact soil characteristics. Natural soil colonization by vegetation or fauna was the major driver in soil modification. The analysis of an intermediate reference showed a delay of multiple decades between vegetation, fauna density, and soil structure improvement, as well as the achievement of a soil of “good biological quality”. We conclude that the use of engineer species on brownfield soil in its actual form is not an early restoration step but should be tested in later steps (e.g., when organic matter content is sufficient). However, additional research is needed in engineer species selection and multi-compartment approaches. A better understanding of the impacts of natural colonization in the early stages of technosol restoration is also essential for restoration techniques’ improvement.